2022
DOI: 10.3389/fcomm.2022.1052355
|View full text |Cite
|
Sign up to set email alerts
|

Using Facebook, Instagram, and Pinterest advertising campaigns to increase enrollment in newborn screening research

Abstract: IntroductionSocial media ad campaigns can be an efficient, cost-effective way to recruit for studies online, especially as the onset of the COVID-19 pandemic limited in-person recruitment. Early Check, a large ongoing study offering testing for a panel of conditions for all newborns in North Carolina, uses social media ad campaigns, along with direct mail, email, print materials in health care settings, and messages through patient portals to contact pregnant women and mothers with eligible newborns. All mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Recently, researchers at RTI experimented with recruitment on Facebook, Instagram, and Pinterest ads to recruit new and expectant parents in North Carolina to sign up for expanded newborn screening. 18 The authors found social media recruitment to be an efficient use of funds when in-person recruitment was not available; however, ad performance and effectiveness depended on several variables. These variables, including ad competition on the platforms, platform ratings of the ad, and tracking capabilities, are often out of the advertiser's control.…”
Section: Original Commentarymentioning
confidence: 99%
“…Recently, researchers at RTI experimented with recruitment on Facebook, Instagram, and Pinterest ads to recruit new and expectant parents in North Carolina to sign up for expanded newborn screening. 18 The authors found social media recruitment to be an efficient use of funds when in-person recruitment was not available; however, ad performance and effectiveness depended on several variables. These variables, including ad competition on the platforms, platform ratings of the ad, and tracking capabilities, are often out of the advertiser's control.…”
Section: Original Commentarymentioning
confidence: 99%